Effects of the neoliberal agenda on academic results at federal universities - Johnatan Rafael Brito; Jéssica Vivianne da Cunha Silva de Brito (Revista Gestão Universitária na América Latina)
With the emergence of debates about the weight of federal public universities' budgets in public accounts, the development of scientific research that present data on such issues to society becomes relevant. In this context, this work sought to identify the effects on the academic performance of Federal Institutions of Higher Education (FIHE) caused by the application of the neoliberal agenda in the budget formation of these institutions. For this purpose, the adopted methodology grouped the universities based on their similarities, using the cluster analysis method, and verified the existence of a correlation between the budget and performance variables. The results found point to a scenario of disruption in FIHE budgets, represented by attacks on the financing model of these institutions under arguments of inefficient performance based on incomplete or biased analyses. In addition, the emergence of the application of neoliberal measures generates signs of a change in the profile of actions carried out within universities, moving from a vanguard place in the generation of scientific knowledge to a kind of service provider in which market demands are met through financial support.